Youth unemployment in transition economies - Marcello Signorelli (IZA World of Labor, 2017)
The 2008 financial crisis and subsequent Great Recession created a second major employment shock in less than a generation in several transition economies. In particular, youth unemployment rates, which are usually higher than adult rates in normal times, reached extremely high levels and partly tended to persist over time. Improving youth labor market performance should therefore be a top priority for policymakers in affected transition countries. Better understanding of the dynamics of national and regional youth unemployment rates and other associated indicators is particularly important for designing effective policy approaches.
Keywords: 330; transition economies; youth unemployment; policies